Seasonal variability of the oxygen minimum zone off Peru in a high-resolution regional coupled model - Vergara, Oscar (2016)
In addition to being one of the most productive upwelling systems, the oceanic region off Peru is embedded in one of the most extensive oxygen minimum zones (OMZs) of the world ocean. The dynamics of the OMZ off Peru remain uncertain, partly due to the scarcity of data and to the ubiquitous role of mesoscale activity on the circulation and biogeochemistry. Here we use a high-resolution coupled physical/biogeochemical model simulation to investigate the seasonal variability of the OMZ off Peru. The focus is on characterizing the seasonal cycle in dissolved O₂ (DO) eddy flux at the OMZ boundaries, including the coastal domain, viewed here as the eastern boundary of the OMZ, considering that the mean DO eddy flux in these zones has a significant contribution to the total DO flux. The results indicate that the seasonal variations of the OMZ can be interpreted as resulting from the seasonal modulation of the mesoscale activity. Along the coast, despite the increased seasonal low DO water upwelling, the DO peaks homogeneously over the water column and within the Peru Undercurrent (PUC) in austral winter, which results from mixing associated with the increase in both the intraseasonal wind variability and baroclinic instability of the PUC. The coastal ocean acts therefore as a source of DO in austral winter for the OMZ core, through eddy-induced offshore transport that is also shown to peak in austral winter. In the open ocean, the OMZ can be divided vertically into two zones: an upper zone above 400 m, where the mean DO eddy flux is larger on average than the mean seasonal DO flux and varies seasonally, and a lower part, where the mean seasonal DO flux exhibits vertical–zonal propagating features that share similar characteristics than those of the energy flux associated with the annual extratropical Rossby waves. At the OMZ meridional boundaries where the mean DO eddy flux is large, the DO eddy flux has also a marked seasonal cycle that peaks in austral winter (spring) at the northern (southern) boundary. In the model, the amplitude of the seasonal cycle is 70 % larger at the southern boundary than at the northern boundary. Our results suggest the existence of distinct seasonal regimes for the ventilation of the OMZ by eddies at its boundaries. Implications for understanding the OMZ variability at longer timescales are discussed.